2017
DOI: 10.3389/fmicb.2017.01563
|View full text |Cite
|
Sign up to set email alerts
|

Role of Age-Related Shifts in Rumen Bacteria and Methanogens in Methane Production in Cattle

Abstract: Rumen microbiota are essential for maintaining digestive and metabolic functions, producing methane as a byproduct. Dairy heifers produce large amounts of methane based on fermentation of digested organic matter, with adverse consequences for feed efficiency and the environment. It is therefore important to understand the influence of host age on the relationship between microbiota and methane production. This study explored the age effect on the relationship between microbial communities and enteric methane p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
42
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(54 citation statements)
references
References 54 publications
6
42
1
Order By: Relevance
“…This is further supported by our findings of higher concentrations of acetate in high CH 4 ‐producing animals. We note that the bacterial taxa identified in this study contrast with those found in previous work that identified Prevotella and Succinivibrio from a comparison of PP heifers (9–10 months of age, similar in age to the PP heifers used in this study) to older cows (45+ months of age) …”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…This is further supported by our findings of higher concentrations of acetate in high CH 4 ‐producing animals. We note that the bacterial taxa identified in this study contrast with those found in previous work that identified Prevotella and Succinivibrio from a comparison of PP heifers (9–10 months of age, similar in age to the PP heifers used in this study) to older cows (45+ months of age) …”
Section: Discussioncontrasting
confidence: 99%
“…We note that the bacterial taxa identified in this study contrast with those found in previous work that identified Prevotella and Succinivibrio from a comparison of PP heifers (9-10 months of age, similar in age to the PP heifers used in this study) to older cows (45+ months of age). 16 Finally, our analysis of the ruminal fungal communities did not identify any putative mitigation targets. This is likely a result of the sampling method, which predominantly represents the liquid portion of the rumen community.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…However, dominant in cattle, Prevotella was not a major in this study. The relative abundance of Prevotella may replace affected by its phylotype or host ages [22]. Luteimonas, found in three group (C_F, C_D, and H_D) is frequently found in diverse environment such as soil, wastewater, and ammonia biofilter [23].…”
Section: Genus (%) Cattle Horsementioning
confidence: 99%
“…It should also be noted that Flavonifractor spp. are more commonly reported in 16S rRNA and metagenome profiling studies performed in animal subjects (Oakley et al, 2014, Medvecky et al, 2018, Zhang et al, 2018a, Borrelli et al, 2017, Liu et al, 2017a, Liu et al, 2018.…”
Section: Chapter 5 General Discussionmentioning
confidence: 95%